Sarcopenic Obesity: A Growing Public Health Concern – A Literature Review - Jocz, Anna Maria; Wagner-Bieleń, Natalia Katarzyna; Zwierzchowska, Martyna; Antoniak , Agata; Centkowska, Anna; Banaśkiewicz, Joanna Karina; Żyta, Aleksandra Maria; Dąbrowska, Gabriela Helena; Żmijewska, Maria Anna; Ziółkowski, Jakub (Quality in Sport, 2025)
Background: Sarcopenic obesity (SO) is a growing clinical and public health concern characterized by the coexistence of excess adiposity and reduced skeletal muscle mass and function. It is increasingly prevalent across various age groups, particularly among individuals with chronic conditions. Methods: This review is based on a narrative synthesis of peer-reviewed literature published between 2015 and 2024. Articles were identified through PubMed, limited to free full-text resources in English. Recent consensus guidelines from the European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Association for the Study of Obesity (EASO) were also included. Results: SO is a multifactorial condition driven by aging, physical inactivity, chronic inflammation, insulin resistance, hormonal changes, oxidative stress, and lipotoxicity. Its prevalence varies widely due to inconsistent diagnostic standards but is notably higher in older adults and those with comorbidities such as type 2 diabetes and cardiovascular disease. Sarcopenic obesity contributes to the development of metabolic disorders, physical limitations, reduced life quality, and an elevated risk of death. Effective management requires a combination of lifestyle interventions, including resistance training, adequate protein intake, and weight management. Conclusion: Early diagnosis and targeted interventions are essential to mitigate the impact of sarcopenic obesity. Further research is necessary to refine diagnostic criteria and develop novel therapeutic approaches to improve outcomes and reduce healthcare burdens.